Comparison of 75g OGTT and Four Sugar Profiles in Diagnosis of Gestational Diabetes Mellitus - Ishtiaq, Yamina; Fakhar, Shazia; Gul, Hina; Sheikh, Darakhshan (Indus Journal of Bioscience Research, 2025)
Objective: Gestational diabetes mellitus (GDM) is a growing issue in Pakistan because of its associations with the adverse maternal and fetal outcomes. This study aimed to evaluate the diagnostic accuracy of the Four Sugar Profile Test compared with the Oral Glucose Tolerance Test (OGTT) which is the current gold standard in detecting GDM. Methods: A descriptive cross-sectional study was conducted by enrolling 260 pregnant women who were between 24-28 weeks gestation at Shifa International Hospital, Islamabad from 1st July 2024 to 31st December 2024. Both the Four Sugar Profile Test (which measures fasting and postprandial glucose levels after meals) and the OGTT were administered to all participants. Sensitivity, specificity, and predictive values were calculated to compare the diagnostic performance of the two tests. Results: The prevalence of GDM was 87.6% using the Four Sugar Profile Test and 91.5% with the OGTT which was taken as gold standard. The Four Sugar Profile Test had a sensitivity of 91.18%, specificity of 50%, a positive predictive value (PPV) of 95.18%, and a negative predictive value (NPV) of 34.38%. The overall diagnostic accuracy was 87.69%. Conclusion: The Four Sugar Profile Test demonstrated a good sensitivity to the OGTT; suggesting it may serve as an alternative diagnostic tool for GDM, especially in settings where the OGTT cannot be done. However, we need further studies to validate the findings and assess long-term maternal and neonatal outcomes for the Pakistan population.